Non-contact electrocardiogram (ECG) smart chair for ST segment elevation myocardial infarction detect - Wali, Tuerxun; Mohd Nor, Rizal; Sidek, Khairul Azami; Abubakar, Adamu (Little Lion Scientific Islamabad Pakistan, 2016)
Myocardial infarction (MI) is a medical term for heart attack. MI are classified into ST-segment elevation MI (STEMI) or non ST-segment elevation MI (NSTEMI). The ST-segment elevation MI (STEMI) can be detected by analyzing the electrocardiography (ECG)result. However, and ECG device is only available in hospitals due to its cost and requires an expert to operate the device. A personal ECG device at home is therefore difficult to be acquired. For most STEMI cases, heart problems requires early detection and medication. Unfortunately, frequent visits to the hospital may not be possible for most people. A new way to have personalized ECG reading without the presence of an expert is therefore desirable. One method is to use a non-contact ECG signal detection technique that could help assess cases of heart problems or an initial apoplectic condition. A non-contact ECG chair framework for STEMI is proposed to empower patients in getting personalized assessment to their heart condition at any time. Patients can easily use the ECG device at the comfort of their home or in the office by just sitting on their chair. The ECG signal will automatically be captured and analyzed to intelligently diagnose the heart condition. The implementation of this concept will help the Malaysian community with early intervention by medical experts and significantly reduce the mortality rate.